A Virtual Laboratory to Improve the Effectiveness of Interactive Learning Media on Science Process Skills and Science Literacy in the Competency Aspects of Dynamic Electricity - Andini Pratiwi M. Mahmud; Mursalin Mursalin; Tirtawaty Abdjul; Masrid Pikoli; Muhammad Yusuf; Abdul Haris Odja (Jurnal Penelitian Pendidikan IPA, 2025)
Implementing interactive learning media based on virtual laboratories is efficacious in improving students' scientific literacy in science learning. This study aims to assess the effectiveness of using interactive learning media based on virtual laboratories in improving students' scientific literacy and science process skills in dynamic electricity in two schools, namely SMP Negeri 1 Kwandang and MTs Al-Khairaat Kwandang, using a guided inquiry learning model. The research design employed was a quasi-experimental design with a pretest-posttest control group. Data was obtained through scientific literacy tests and observation sheets for science process skills. The study's results showed that interactive learning media based on virtual laboratories were effective in enhancing students' scientific literacy and science process skills. The results of the N-Gain analysis for scientific literacy showed an average score of 0.72, indicating a high category. Meanwhile, the results of the observations showed an increase in the achievement of science process skills at each meeting, particularly for the indicators of observing and conducting experiments, which improved to the very good category. Additionally, the results of the t-test on scientific literacy revealed a statistically significant difference (p < 0.05), indicating a significant difference between the pre- and post-learning periods. Thus, interactive learning media based on virtual laboratories assisted by guided inquiry models have been proven effective in improving students' scientific literacy and science process skills